Impact of the SGLT2 inhibitor empagliflozin on urinary supersaturations in kidney stone formers (SWEETSTONE trial): protocol for a randomised, double-blind, placebo-controlled cross-over trial. Issue 3 (14th March 2022) - Schietzel, Simeon; Bally, Lia; Cereghetti, Grazia; Faller, Nicolas; Moor, Matthias B; Vogt, Bruno; Rintelen, Felix; Trelle, S; Fuster, Daniel
Abstract : Introduction: Kidney stones are a global healthcare problem. Given high recurrence rates and the morbidity associated with symptomatic stone disease, effective medical prophylaxis is clearly an unmet need. Explanatory analyses of randomised controlled trials with sodium/glucose cotransporter isoform 2 inhibitors indicated a 30%–50% reduced rate of stone events in patients with diabetes. Underlying mechanisms remain unclear. We aim to determine the effect of empagliflozin on urinary supersaturations in non-diabetic kidney stone formers to evaluate their therapeutic potential for recurrence prevention. We will provide first clinical trial evidence on whether urinary supersaturations are affected by empagliflozin in kidney stone formers. Methods and analysis: The SWEETSTONE trial is a randomised, double-blind, placebo-controlled, cross-over, exploratory study to assess the impact of empagliflozin on urinary supersaturations of calcium oxalate, calcium phosphate and uric acid in kidney stone formers. We plan to include 46 non-diabetic adults (18–74 years) with ≥1 past kidney stone event and stone composition with ≥80% of calcium or ≥80% of uric acid. Patients with secondary causes of kidney stones or chronic kidney disease will be excluded. Eligible individuals will be randomised in equal proportions to receive either a 14-day treatment with 25 mg empagliflozin followed after the 2–6 weeks wash out period by a 14-day treatment with a matching placebo or the reverse procedure. Secondary outcomes will include electrolyte concentrations, renal function, mineral metabolism and glycaemic parameters, urinary volume and safety. Results will be presented as effect measures (95% CIs) with p values and hypothesis testing for primary outcomes (significance level 0.02). Ethics and dissemination: The SWEETSTONE trial was approved by the Swiss ethics committee and Swissmedic. First results are expected in the fourth quarter of 2022. Trial registration number: NCT04911660; Pre-results .